PENGEMBANGAN APPLICATION SERVICE DATA MAHASISWA PADA WEBSITE JURUSAN ILMU KOMPUTER - Mardhi Nopriyansah; Dwi Sakethi; Didik Kurniawan (Jurnal Pepadun, 2021)
The information system at the Department of Computer Science, University of Lampung has some data such as data about students, lecturers, courses schedule and  final assignments or theses. The information system contained in the Computer Science Department, University of Lampung is still not integrated between one system and another. This makes the existing data inconsistent so that there are some differences in data between systems. To solve this problem, a student data Application Service Interface (API) program with Representational Transfer State (REST) architectural style was created. Framework CodeIgniter (CI) will be used in the development of this application using the waterfall method. This research has succeeded in building thirteen APIs and tested using Postman software. System testing is also carried out using the equivalence partitioning method and system functional testing. Based on testing with the equivalence partitioning method and system functional testing, overall success was obtained at each API access point. The results of the API access will be sent in the Javascript Object Notation (JSON) data format.